POTENSI SEKTOR PARIWISATA KABUPATEN GUNUNG MAS SELAMA PANDEMI COVID-19 - Mayang Pradina Putri; Agung Eddy Suryo Saputro (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
At the beginning of 2020, the Covid-19 Pandemic began to hit the world and Indonesia. The Covid-19 Pandemic has caused the economy in Indonesia to become weak, including the economy of Gunung Mas Regency. The most affected sector by the Covid-19 Pandemic is the tourism sector. This study aims to examine the economic and tourism potential of Gunung Mas Regency during the Covid-19 Pandemic. The analytical method that used in this research is Klassen Typology Analysis and Location Quotient. The results of this study indicate that there are four GDP sectors which have economic potential in Gunung Mas Regency. The four GDP sectors are Mining and Quarrying; Wholesale and Retail Trade, Car and Motorcycle Repair, Government Administration; and Education. In addition, this study also shows that Beauty and Health Products have tourism potential in Gunung Mas Regency. The right strategy to develop Beauty and Health Products is Promotion and Expansion.